Propaganda und Manipulation in der Sprache Anhand der offiziellen Stellungnahmen des Russischen Aussenministeriums: Zum Russland-Ukraine-Krieg (2022) (Politeja, 2023)
THE PROPAGANDA AND LINGUISTIC MANIPULATION IN THE LANGUAGE OF POLITICS ON THE BASIS OF THE OFFICIAL STATEMENTS OF THE RUSSIAN FOREIGN OFFICE ABOUT THE RUSSIAN INVASION OF UKRAINE (2022)Persuasion, disinformation, manipulation, censorship, which are elements of propaganda, can be regarded as central terms of the language of politics, especially during conflict situations and wars. The question of interest is in what ways the specific language techniques are used by the Russian Foreign Affairs Department for the purposes of propaganda in the context of the 2022 Russian invasion of Ukraine. The paper analyzes the official statements of Maria Zakharova, the Director of the Information and Press Department of the Ministry of Foreign Affairs of the Russian Federation that are available on the web page of the Embassy of Russia in Berlin. The following examinations are confronted with the well-documented nature of the persuasive language in Nazi propaganda before and during World War II. The aim of such analysis is to examine in what ways and to what extent the specific propaganda techniques they are used to justify the war that Russia has started by invading Ukraine.